The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1097/aog.0000000000003489
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Fetal Anatomic Ultrasound Examination Duration and Association With Body Mass Index

Abstract: OBJECTIVE: To evaluate the association of the duration of the detailed fetal anatomic ultrasound examination with maternal body mass. METHODS: This was a retrospective chart review of patients presenting to our clinic for detailed fetal anatomic examinations between January 1, 2010, and June 30, 2017. After excluding multifetal pregnancies and other examinations expected to have a longer duration, a total of 6,522 examinations were performed between 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…A prior analysis of these data showed that there is a positive relationship between the detailed fetal anatomic examination duration and a rising maternal BMI. 17 This finding is similar to prior studies suggesting that obesity was associated with increased time needed to complete a first-trimester screen 14,15 and contrasts with the findings of Romary et al, 35 which did not show these differences in the examination duration between gravidae of various BMIs for either a firstor second-trimester ultrasound examination.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…A prior analysis of these data showed that there is a positive relationship between the detailed fetal anatomic examination duration and a rising maternal BMI. 17 This finding is similar to prior studies suggesting that obesity was associated with increased time needed to complete a first-trimester screen 14,15 and contrasts with the findings of Romary et al, 35 which did not show these differences in the examination duration between gravidae of various BMIs for either a firstor second-trimester ultrasound examination.…”
Section: Discussionsupporting
confidence: 85%
“…The frequency of suboptimal examinations was shown to increase with higher maternal prepregnancy BMI classes, consistent with prior studies. [8][9][10][15][16][17][18][25][26][27][28][29][30][31][32][33] Although not explored in Values in parentheses are 95% confidence intervals. this study, prior approaches to combat this issue have suggested that an earlier scan in addition to the standard 20-week anomaly scan has higher completion rates in obese women at the cost of increased resource use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sonography in the super obese population can be difficult, as the amplitude diminishes as sound propagates through the body, making images hard to obtain and interpret. In a recent retrospective study, the anatomic survey in patients with super obesity took 13.5 minutes longer than patients with normal BMI 7 . Multiple prior studies have found that as BMI increases, the completion rate of the anatomic survey decreases and the number of studies required to complete the evaluation increases 8‐10 .…”
Section: Introductionmentioning
confidence: 99%